Experimental and Numerical Analysis of Metal Radiated by an Infra-Red Heater - Mohd Zaidi, Sidek; Syahidan, Kamaruddin (2016)

(untitled)
In this paper, an experimental and numerical technique have been used to study heat generation of mild steel plate radiated by an infra-red heater. Initially, an experiment has been conducted to determine temperature distribution at the selected points on the workpiece. Then, a finite element model (FEM) has been developed to replicate the conducted test. Thermal distribution results from FEM shows good agreement with the experiment results. The result proves the validaty of all the input parameters in the developed FEM model.